Efficacy of Indigenous Crude Plant Extracts against Rice Weevil, Sitophilus oryzae L. 1763 (Coleoptera: Curculionidae): Crude plant extracts against rice weevil - Imran, Muhammad; Bashir, Lubna; Kubar, Muhammad Ibrahim; Rind, Sajjad Hussain; Sahto, Jam Ghulam Mustafa; Gilal, Arfan Ahmed; Mangi, Sanaullah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Rice weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae) is a widely distributed and major insect pest of rice that causes considerable losses to both husked and unhusked rice grains. Plant-based pesticides are alternative to synthetic pesticides in managing stored product pests owing to their severe hazardous effects. Thus, locally available plant leaf crude extracts i.e., neem (Azadirachta indica A. Juss 1830), turmeric (Curcuma longa L. 1753), and mint (Mentha longifolia L. Huds. 1762) were investigated at 2 % (w/w) concentration against S. oryzae in unhusked and husked rice. Adult mortality was recorded at 24, 48 hours, and seven days after the application whereas, population build-up was recorded at 1-, 2-, and 3-months intervals. Overall and grain weight loss was also recorded at the end of the experiment. In husked and unhusked rice, the highest mortality percentage was observed in turmeric powder (93.30 %) and neem (80.00 %), respectively. In comparison to plant extracts, relatively higher population growth of S. oryzae was recorded in control husked and unhusked rice. At the end of the 3rd month, the highest and lowest population in husked rice grains was recorded in control (70.67 ± 3.18) and turmeric treatments (18.00 ± 2.65), respectively, whereas control and neem treatments exhibited the highest (83.67 ± 3.28) and lowest (39.67 ± 2.33) populations in unhusked rice. The lowest grain weight loss in husked and unhusked rice was recorded in turmeric (9.33 %) and neem (16.67 %), respectively. Thus, turmeric and neem extracts should be investigated on large scale under commercial warehouses for the management of S. oryzae in husked and unhusked rice.